Development of novel PP2A activators for use in the treatment of acute myeloid leukaemia. Issue 20 (22nd April 2016) - Toop, Hamish D.; Dun, Matthew D.; Ross, Bryony K.; Flanagan, Hayley M.; Verrills, Nicole M.; Morris, Jonathan C.
Abstract : The synthesis and biological evaluation of new cytotoxic analogs of AAL(S) are reported. Our findings identify key structural motifs required for anti-cancer effects. Abstract : AAL(S), the chiral deoxy analog of the FDA approved drug FTY720, has been shown to inhibit proliferation and apoptosis in several cancer cell lines. It has been suggested that it does this by activating protein phosphatase 2A (PP2A). Here we report the synthesis of new cytotoxic analogs of AAL(S) and the evaluation of their cytotoxicity in two myeloid cell lines, one of which is sensitive to PP2A activation. We show that these analogs activate PP2A in these cells supporting the suggested mechanism for their cytotoxic properties. Our findings identify key structural motifs required for anti-cancer effects.